Investigating a semi-continuous synthetic pathway for the preparation of the antiretroviral drugs tenofovir disoproxil and tenofovir alafenamide - Riley, Darren Lyall (University of Pretoria, 2022)
Dissertation (MSc (Chemistry))--University of Pretoria, 2021.